Diseño de un sistema de riego estacionario por aspersión para una superficie de 10 440 m2 para el Estadio Rafael Cabrera de San Miguel de Urcuquí - Salas Quelal, Joao Sebastian (2017)
The development of this project is to design a sprinkler irrigation system for an area of 10 440 square meters for the “Rafael Cabrera” Stadium located in San Miguel de Urcuquí. First at all, by means of a field diagnosis the current state of the irrigation system of the stadium is described in detail since its water resources will be used for the development and implementation of this project. The configuration of the system was determined taking into consideration the geometry of the playing field; the dimensioned the main pipe, 5 secondary lines or branches, and the sprinklers have been selected based on the information provided by planimetric assessment of the stadium. The water application consists of watering a single branch at a time; this requires 887.6 l / min and 6 bars. By applying the general energy equation, the system curve was obtained by Darcy - Weisbach’s analytical tool. In this way, the pumping group was selected, consisting of a centrifugal electric pump and a hydropneumatic tank that meet the hydraulic requirements of the system. The design capability of the sprinkler irrigation system is quantitatively exposed by an analysis comparing both the current system and the new design developed in this project. The results obtained indicate optimization in the time of operation, greater water use, reduction of losses due to surface runoff, greater efficiency of design, and saving of economic resources by operation.